Frequency, risk factors, and outcomes of non-occlusive mesenteric ischaemia after cardiac arrest. (December 2020) - Paul, Marine; Bougouin, Wulfran; Legriel, Stéphane; Charpentier, Julien; Jaubert, Paul; Savary, Guillaume; Bourcier, Simon; Pène, Frédéric; Dumas, Florence; Grimaldi, David; Cariou, Alain
Abstract: Purpose: Mesenteric ischaemia after successfully resuscitated cardiac arrest (CA) has been insufficiently studied. We aimed to assess the frequency, risk factors, and outcomes of non-occlusive mesenteric ischaemia (NOMI) after CA. Methods: We retrospectively included patients admitted to a CA centre with sustained return of spontaneous circulation between 2007 and 2017. NOMI was suspected based on clinical symptoms and classified as possible if no tests were feasible or the only test was a negative abdominal computed tomography (CT) scan and as confirmed if diagnosed by endoscopy, CT, or surgery. Results: Of 1343 patients, 82 (6%) had suspected NOMI, including 33 (2.5%) with confirmed NOMI. Investigations for suspected NOMI were done in 47/82 (57%) patients (CT, n  = 30; lower digestive endoscopy, n  = 14; and upper digestive endoscopy, n  = 12); 11 patients underwent surgery. By multivariate analysis, factors associated with suspected NOMI were female sex (OR, 1.8; 95%CI, 1.1–2.9, p  = 0.02), cardiovascular comorbidities (OR, 1.6; 95%CI, 1.0–2.7; p  = 0.047), admission lactate >5 mmol/L (OR, 2.0; 95%CI, 1.2–3.4; p  = 0.01), low flow >17 min (OR, 2.2; 95%CI, 1.3–3.8; p  = 0.003), and inotropic score >7 μg/kg/min (OR, 1.8; 95%CI, 1.1–3.2; p  = 0.03). ICU mortality was 96% (79/82), with 61% of patients dying from multi-organ failure (MOF) and 35% from post-anoxic brain injury. Of the eight patients who regained consciousness, 5 finally died from MOF, leaving 3 patients discharged alive from the ICU with a good neurologic outcome. Conclusions: NOMI may affect 2.5–6% of patients after CA. Mortality was extremely high in patients, and very few survived with a good neurological outcome.